The Use of Foot of the Green-Lipped Mussel is Perna Viridis as an Alternative Method to Reduce the Gender Effect on the Bioaccumulation of Cu and Zn in the Mussel - Chee Kong Yap; Yew Jeng Eugene Ng; Franklin Berandah Edward Thomas; Wan Hee Cheng; Ghim Hock Ong (Annals of Limnology and Oceanography - Peertechz Publications, 2016)
In this study, the green-lipped mussels Perna viridis were collected from a high activity sampling at Senibong in the Straits of Johore and two relatively clean sites with fi sh aquacultural activity at Bagan Tiang (Perak) and Sg. Semerak (Kelantan). The mussels were dissected by gender into byssus, crystalline style, foot, gill, gonad, mantle and muscle. By gender, these pooled and dissected soft tissues and total soft tissues were determined for Cu and Zn. The variabilities of both metals between male and female were investigated by using coeffi cient of variation (CV). It is found that the low CV values among all the dissected soft tissues was foot, indicating a more accuracy in the biomonitoring of Cu and Zn using P. viridis's foot. This suggests that foot of P. viridis can be used as an alternative method to reduce the gender effect on the bioaccumulation of Cu and Zn.